2023
DOI: 10.1136/svn-2022-002185
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of futile recanalisation after endovascular therapy in acute vertebrobasilar artery occlusion patients: insight from the ANGEL-ACT registry

Dapeng Sun,
Xinguang Yang,
Xiaochuan Huo
et al.

Abstract: ObjectivesTo identify the occurrence rate and predictors of futile recanalisation after endovascular therapy (EVT) for acute vertebrobasilar artery occlusion (VBAO).MethodsParticipants of the Endovascular Treatment Key Technique and Emergency Workflow Improvement of Acute Ischaemic Stroke (ANGEL-ACT) registry were selected for the analysis. Futile recanalisation was defined as patients did not achieve a 90-day good outcome (modified Rankin Scale ≤3) despite successful recanalisation (modified Treatment in Cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, a previous study proposed a BATMAN score of 3 as the optimal threshold for predicting FR following EVT in BAO stroke. 34 Moreover, a recent BASILAR sub-study showed that although patients with lower BATMAN scores (0-3 and 4-6) had worse functional outcomes than those with higher scores (7)(8)(9), they could still benefit from EVT compared to BMM. 35 These conflicting findings underscore the need for future research to determine the feasibility of using specific BATMAN score thresholds in identifying BAO patients amenable to EVT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a previous study proposed a BATMAN score of 3 as the optimal threshold for predicting FR following EVT in BAO stroke. 34 Moreover, a recent BASILAR sub-study showed that although patients with lower BATMAN scores (0-3 and 4-6) had worse functional outcomes than those with higher scores (7)(8)(9), they could still benefit from EVT compared to BMM. 35 These conflicting findings underscore the need for future research to determine the feasibility of using specific BATMAN score thresholds in identifying BAO patients amenable to EVT.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, real-world registry studies have revealed that despite achieving successful recanalization (modified Thrombolysis in Cerebral Infarction [mTICI] grade ≥ 2b), approximately 47.0-62.8% of BAO patients still exhibit unfavorable outcomes (modified Rankin Scale score [mRS] > 3) at 90 days after EVT. [4][5][6][7] The underlying mechanisms of this phenomenon known as futile recanalization (FR) remain incompletely clear. Therefore, the identification of risk factors or predictors for FR is crucial in assisting clinicians in selecting appropriate BAO patients for EVT and developing tailored patient management strategies.…”
Section: Introductionmentioning
confidence: 99%